25th ANNIVERSARY OF CLONING BY SOMATIC-CELL NUCLEAR TRANSFER: Current applications of SCNT in advanced breeding and genome editing in livestock. Issue 1 (11th June 2021) - Galli, Cesare; Lazzari, Giovanna
Abstract : SCNT (somatic cell nuclear transfer) has complemented the toolbox of ARTs offering yet another technique to reproduce animals in an unprecedented way. Despite remarkable achievements, SCNT suffers low efficiency, high pregnancy losses and higher than normal stillbirth rates that makes it an expensive technique to reproduce animals. Moreover, due to welfare issues associated with gestation and the newborn offspring, it is banned in some countries. It has become evident that these problems are of epigenetic nature associated with incomplete genome reprogramming, observed more frequently in ruminants and less often and of minor degree in pigs and horses. Genome editing is enormously benefiting from SCNT to turn genome edited cells into animals, even if zygote microinjection of CRISPR/Cas9 will become an alternative route in some occasions. SCNT will also be a route to reprogram somatic cell to pluripotency since bona fide iPSC in livestock are missing while embryonic stem cells have been now established. This opens the way to other technologies like the development of artificial gametes or interspecies nuclear transfer. To strengthen its commercial applications, SCNT will face three major challenges, that is, intellectual property (extremely unclear in genome editing), regulatory approval by the relevant authorities of the resuting potential products and finally, acceptance by the public who will eventually decide with its behavior the life or the death of the technology.